Structural Classification of Basalt FRP at High Temperatures - Sudhir Vummadisetti; Sesha Ratnam Pasalapudi; Santosh Kumar Gottapu; Kranthi Kumar Goriparthi; Areda Batu (Advances in Materials Science and Engineering)
In this study, two different temperatures are considered to verify the mechanical response of basalt fiber-reinforced polymer specimens. Initially, fibers are subjected to 300°C temperature for 4 hours and 600°C temperature for 2 hours in an electrical muffle furnace effectively. Later, laminates were prepared with these fibers and machined into test strips to verify their mechanical properties by conducting tensile and flexural tests. These laminates were compared with specimens prepared with normal fibers, i.e., fibers without temperature treatment. Moreover, the ductility and elastic behavior of the basalt fiber-laminated specimens are studied to figure out the possible structural applications. The residual stress of specimens subjected to 300°C temperature under tensile loading is about 84%, whereas for 600°C temperature, it is only 13% of maximum stress. A similar trend has been observed for specimens tested under flexural loading condition. Hence, it is concluded that the basalt fiber-reinforced polymer laminate can withstand and depict satisfactory results up to 300°C elevated temperature irrespective of time.